'Females Don't Need to be Reluctant': Employing Design Thinking to Harness Creative Confidence and Interest in STEAM. (27th August 2020) - Kijima, Rie; Sun, Kathy Liu
Abstract: There is great gender gap in mathematics and science among countries around the world, but the gender gap is one of the largest in Japan. In order to address this issue, we evaluated an educational intervention to empower the next generation of female youths by employing design thinking to ignite their interests in Science, Technology, Engineering, Arts and Mathematics (STEAM) fields. In this article, we explain the rationale for the intervention, describe the unique three‐day curriculum employing design thinking, and share the results from the intervention. There are four key findings of our study. After participating in the workshop, the middle school female students showed greater interest in STEAM fields, demonstrated increased levels of creative confidence, cultivated a greater sense of empathy for others, and exhibited greater appreciation for collaboration. This study highlights the possibilities and opportunities for using design thinking to encourage female youths to become more interested in STEAM fields.